2007
DOI: 10.1111/j.1740-1461.2007.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

What Explains Dissent on the High Court of Australia? An Empirical Assessment Using a Cointegration and Error Correction Approach

Abstract: This article examines the factors influencing the annual dissent rate on the High Court of Australia from its first full year of operation in 1904 up to 2001 within a cointegration and error correction framework. We hypothesize that institutional factors, socioeconomic complexity, and leadership style explain variations in the dissent rate on the High Court of Australia over time. The institutional factors that we consider are the Court's caseload, whether it had discretion to select the cases it hears, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…In contrast to the breadth and depth of research that refers to the attitudinal model or the neo‐institutional model in the U.S. Supreme Court, not many similar studies have been conducted in high courts outside the United States. Among the exceptions are Smyth's (2005), Narayan and Smyth's (2007), and Wood's (2001) research on decision making in the Australian High Court, and Ostberg and Wetstein (1998, 1999, 2007; Wetstein et al. 2009), and Alarie and Green (2007), who focused on attitudinal decision making in the Canadian Supreme Court 1…”
Section: Comparative Studies On Attitudinal and Neo‐institutionamentioning
confidence: 99%
“…In contrast to the breadth and depth of research that refers to the attitudinal model or the neo‐institutional model in the U.S. Supreme Court, not many similar studies have been conducted in high courts outside the United States. Among the exceptions are Smyth's (2005), Narayan and Smyth's (2007), and Wood's (2001) research on decision making in the Australian High Court, and Ostberg and Wetstein (1998, 1999, 2007; Wetstein et al. 2009), and Alarie and Green (2007), who focused on attitudinal decision making in the Canadian Supreme Court 1…”
Section: Comparative Studies On Attitudinal and Neo‐institutionamentioning
confidence: 99%
“…Empirical studies associated with different theoretical approaches suggest that indeed caseloads affect judicial decisions in both form (disposition type) and substantive case outcomes. With regard to modes of disposition, Epstein et al (2013) showed that high caseloads encourage judges to employ doctrines that allow early dismissal of cases, such as standing and ripeness, and deter judges from engaging in the time-consuming task of writing dissents (also see Epstein et al 2011, Narayan & Smyth 2007. High caseloads were also found to reduce the volume of cases that go to full trial (Galanter 2004).…”
Section: B Micro Judicial-behavior Level: What Do Judges Maximize?mentioning
confidence: 99%
“…Canadian justices' attitudinal behavior varies between issue areas, both in terms of ideological dimensions and the degree of attitudinal impact (Wetstein et al ), and moderately correlates with ideological point estimates (Alarie & Green ). In Australia, there is a significant correlation between justices' dissent rates and their ideology, measured with the political party as proxy (Smyth & Narayan ). Attitudinal studies of the Philippine Supreme Court, using demographic background, political party of the appointing president, and recently utilizing ideal point measurement, show mixed degrees of attitudinal behavior across presidential terms and in different political contexts (Tate & Haynie ; Haynie ; Escresa & Garoupa ; Dalla Pellegrina et al ).…”
Section: Modeling a Dcammentioning
confidence: 99%
“…Judicial behavior varies between mandatory and discretionary dockets, with important cases more typical of the latter (Eisenberg et al ). Caseloads affect the amount of resources available to be invested in each case, as well as the cost of registering dissent (Smyth & Narayan ; Sommer , ; Epstein et al ).…”
Section: Testing Dcam and Ideological Ideal Point Preference (Iipp) Imentioning
confidence: 99%